If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8 + -5y = 15 + -1d Solving -8 + -5y = 15 + -1d Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -5y = 15 + 8 + -1d Combine like terms: -8 + 8 = 0 0 + -5y = 15 + 8 + -1d -5y = 15 + 8 + -1d Combine like terms: 15 + 8 = 23 -5y = 23 + -1d Divide each side by '-5'. y = -4.6 + 0.2d Simplifying y = -4.6 + 0.2d
| 24+3+12x=10+4x-3x | | 10+971(1673%10)= | | x^3-6x^2-3x-16=0 | | x^3-6x^2-3x-10=0 | | 3.2z=14 | | x^3-6x^2+3x-16=0 | | 8y+8-3y+6=2y+14 | | 44x=32x | | 3=7b+13-2b | | 6=-2n+s | | 4x^2+6x-2=x^2-2x+1 | | 4x^2+6x-2=x^2-2x+2 | | kx^2+12x+12=0 | | 0=8x-(3-z) | | -y-8+8y=-9+5y+1 | | 2x-6-4x-16=4x-1*3 | | 6a-11=19 | | 3x^2-kx+30=0 | | 6*(-1)=7-4y | | 2*x+4=6 | | -8(x-4)=4(x-12) | | 1+5x-2x=-2+3x+15x | | (.02)35+.09(x)=.04(35+x) | | -9+9x-5x-x=6+x-x | | 4(-8r+5)=-32r-26 | | 27=5r+2 | | 75-3x=10x-23 | | 4-(2x)=12 | | 20x=15(x+5) | | x+12=28x+3 | | (23x+11)=(14x+21) | | 2x+24=10x-24 |